A Versatile Strategy for Unimolecular Micelle-Derived Hollow Polymer Nanoparticles as General Nanoreactors - Yan, Kailong (Langmuir : the ACS journal of surfaces and colloids, 2020)
We reported the synthesis of a well-defined hollow polymer nanoparticle derived from star-shaped unimolecular micelles. β-Cyclodextrin was first applied as an efficient macroinitiator to prepare a star-shaped PCL via ring-opening polymerization (ROP). Then, the star-shaped PCL was modified to be a macro-RAFT agent for photoinduced electron/energy transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization of S-Cl monomers. The prepared unimolecular micelles can be photocross-linked under UV irradiation after a simple nucleophilic substitution reaction, which made -Cl groups to be -N3 groups. After the selective removal of the PCL core, hollow polymer nanoparticles were achieved and exhibited to be a general nanoreactor strategy for the fabrication of nanocrystals with well-controlled architectures. Compared with unimolecular micelle templates, the nanocrystals prepared by hollow templates are absolutely pure as no polymer chains are embedded in the inorganic nanocrystals. In addition, by changing the concentration of the precursor, the structure of the nanocrystal can be changed from a normal spherical structure to a hollow structure